2022
DOI: 10.1101/2022.12.06.519418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EEG error-related potentials encode magnitude of errors and individual perceptual thresholds

Abstract: Error-related potentials (ErrP) are a prominent electroencephalogram (EEG) correlate of performance monitoring, and so crucial for learning and adapting our behavior. Although there exists an agreement that ErrP signal awareness to errors, it remains poorly understood whether they encode further information. Here we report an experiment with sixteen participants during three recording sessions in which occasional visuomotor rotations of varying magnitude occurred during a cursor reaching task. We designed a br… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Previous studies showed that ErrPs encode subjective aspects of performance monitoring such as consciousness 77,78 , confidence 79 and individual ability to perceive errors 80 . In ErrP-based BMI applications, ErrP decoding probabilities were exploited to teach (quasi) optimal policies to external agents 14,19,81,82 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that ErrPs encode subjective aspects of performance monitoring such as consciousness 77,78 , confidence 79 and individual ability to perceive errors 80 . In ErrP-based BMI applications, ErrP decoding probabilities were exploited to teach (quasi) optimal policies to external agents 14,19,81,82 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we focused on EEG-based ERPs as a candidate neural signature that emerges in response to transient sensory perturbation (Maidhof et al, 2010; Strübing et al, 2012; Sammler et al, 2013; Bianco et al, 2016). ERPs are characterized by specific patterns of EEG activity in response to particular stimuli or events, encoding valuable neural information about the processing of cognitive, sensory, and motor functions (Polich, 2007; van Dinteren et al, 2014; Hirano et al, 2020; Iwane et al, 2023). This neural index enables us to shed light on cognitive and sensorimotor processes.…”
Section: Discussionmentioning
confidence: 99%
“…This neural index enables us to shed light on cognitive and sensorimotor processes. ERPs can be analyzed to identify components based on their latency from the onset of particular stimuli or events (Squires et al, 1975; van Dinteren et al, 2014; Iwane et al, 2023). Among them, we drew attention to the observations of the N180 and P300 components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations